ChemInform Abstract: Hexagonal RMnO3: A Model System for 2D Triangular Lattice Antiferromagnets. Issue 32 (22nd July 2016) - Sim, Hasung; Oh, Joosung; Jeong, Jaehong; Le, Manh Duc; Park, Je‐Geun
Abstract: Review: 122 refs.